2020
DOI: 10.1115/1.4048490
|View full text |Cite
|
Sign up to set email alerts
|

Wind Turbine Multivariate Power Modeling Techniques for Control and Monitoring Purposes

Abstract: Wind turbine performance monitoring is a complex task because the power has a multivariate dependence on ambient conditions and working parameters. Furthermore, wind turbine nacelle anemometers are placed behind the rotor span and the control system estimates the upwind flow through a nacelle transfer function: this introduces a data quality issue. This study is devoted to the analysis of data-driven techniques for wind turbine performance control and monitoring: operation data of six 850 kW wind turbines site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 23 publications
1
22
0
Order By: Relevance
“…For these reasons, in order to compare reliably the performance of the same model of wind turbine placed in different sites, it is more appropriate to compare operation curves that are not based on the nacelle wind speed measurements: in this study, the same curves as in [25] are selected, which are the generator speed-power curve and the blade pitchpower curve. In studies like [34][35][36], it was observed that operation variables as the rotor speed, generator speed, and blade pitch are important for a reliable multivariate analysis of the power of a wind turbine [37,38]. In this study, following [38], a step forward with respect to the literature is made because the selected curves involve couples of operation variables and do not involve the nacelle wind speed.…”
Section: Operation Curve Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…For these reasons, in order to compare reliably the performance of the same model of wind turbine placed in different sites, it is more appropriate to compare operation curves that are not based on the nacelle wind speed measurements: in this study, the same curves as in [25] are selected, which are the generator speed-power curve and the blade pitchpower curve. In studies like [34][35][36], it was observed that operation variables as the rotor speed, generator speed, and blade pitch are important for a reliable multivariate analysis of the power of a wind turbine [37,38]. In this study, following [38], a step forward with respect to the literature is made because the selected curves involve couples of operation variables and do not involve the nacelle wind speed.…”
Section: Operation Curve Analysismentioning
confidence: 99%
“…In studies like [34][35][36], it was observed that operation variables as the rotor speed, generator speed, and blade pitch are important for a reliable multivariate analysis of the power of a wind turbine [37,38]. In this study, following [38], a step forward with respect to the literature is made because the selected curves involve couples of operation variables and do not involve the nacelle wind speed. In [25], it has been observed that the above curves should be interpreted in light of the control of the wind turbines: for moderate wind speed (approximately 5 ≤ v ≤ 9 m/s), wind turbines operate with a variable rotational speed and fixed pitch; for higher wind speeds (approximately 9 ≤ v ≤ 13 m/s), the rotational speed is rated and the blade pitch varies.…”
Section: Operation Curve Analysismentioning
confidence: 99%
“…From Table 3 it arises that the average error metrics can be considered particularly robust because their standard deviation is very low. Furthermore, as regards the power P it is possible to compare the literature: the order of the error metrics is similar to the results collected in [36] for the same test case. Therefore it can be stated that the dimension reduction through the PCA does not affect remarkably the quality of the regression and helps highlighting the dependence of the target on the orthogonalized input variables matrix.…”
Section: Resultsmentioning
confidence: 99%
“…This inspires as further direction to adopt a similar approach also for multivariate wind turbine power curve modelling: actually, there is a wide literature about the improvement of the model structure, while the discussion about the use of further covariates is at its early stages. In [24,25,[27][28][29], multivariate models for the power curves have been proposed, which include further environmental and operation variables with respect to solely the average nacelle wind speed, but at present there are no studies dealing with the inclusion in the models of minimum, maximum and standard deviation of the main variables. Finally, it would be extremely interesting to analyze the operation curves selected in this study by using time-resolved wind turbine data [47] having much lower sampling time (order of seconds).…”
Section: Resultsmentioning
confidence: 99%
“…The simplest data-driven model employed for wind turbine performance monitoring is the power curve [20][21][22][23], which is the relation between the average wind speed and the extracted power. On the grounds of the above discussion, a recent trend in wind energy literature regards multivariate approaches to the power curve: in [24][25][26], the point of view is including additional environmental variables (either measured ambient temperature, humidity, and wind direction as in [24] or estimated by a Numerical Weather Prediction model as in [25]); in [27][28][29][30], the approach consists in including the most important operation variables (as the blade pitch and the rotor speed) in the multivariate modelling of the power curve.…”
Section: Introductionmentioning
confidence: 99%